2012
DOI: 10.1111/j.1747-7379.2012.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Immigrant Employment Sequences in the First Years of Settlement

Abstract: Drawing on data from the Longitudinal Survey of Immigrants to Canada, we analyze factors shaping new immigrants' month-bymonth employment trajectories over their first 4 years of settlement. We treat trajectories as multidimensional and holistic entities, seeking to predict the correlates of a set of typical pathways identified via optimal matching techniques and cluster analysis. Human capital attributes and household context shapes trajectories in important ways, but patterns related to bias and discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 79 publications
4
75
0
Order By: Relevance
“…As previously highlighted, for most participants these pathways were by no means linear but necessarily fluid, as individuals continually assessed their progress towards their goal and took steps to address any barriers that they encountered. The various barriers migrants encounter in their search for work have been widely documented in the literature (Chaze & George, 2013;Constable et al, 2004;Fuller & Martin, 2012;Reitz, 2007;Zuberi & Ptashnick, 2012) and, on the whole, the findings in this study support previous research. The main barriers are briefly outlined below.…”
Section: Pathway Progressionsupporting
confidence: 89%
See 2 more Smart Citations
“…As previously highlighted, for most participants these pathways were by no means linear but necessarily fluid, as individuals continually assessed their progress towards their goal and took steps to address any barriers that they encountered. The various barriers migrants encounter in their search for work have been widely documented in the literature (Chaze & George, 2013;Constable et al, 2004;Fuller & Martin, 2012;Reitz, 2007;Zuberi & Ptashnick, 2012) and, on the whole, the findings in this study support previous research. The main barriers are briefly outlined below.…”
Section: Pathway Progressionsupporting
confidence: 89%
“…Language proficiency is one of the most widely cited barriers to both qualifications recognition and labour market entry (Cheng et al, 2013;Colic-Peisker, 2009a;Fuller & Martin, 2012;Grenier & Xue, 2011;Visintin et al, 2015;Waxman, 2001) and Hawthorn (2015) has found that the use of language tests acted to delay registration, a finding supported by the current study. This was a significant issue for a number of participants, particularly those on family reunion visas, who had not had to undergo pre-migration language testing.…”
Section: The Demonstration Of Competencesupporting
confidence: 73%
See 1 more Smart Citation
“…On the other hand, parents using "accomplishment of natural growth", provide less structure for their children (they hang out with them or their other kin), have little discussion and rarely allow questioning, and show a sense of powerlessness when it comes to negotiating with institutions. There is indeed evidence that concerted cultivation mediates the effect of family background on educational achievement & Amato, 2011;Cheadle, 2009;Martin, 2012). In determining to what extent parental resources or parental socialization, it is important to the distinguish different dimensions of parental SES, by examining both the effect of parental income and education (Amato et al, 2015).…”
Section: Family Backgroundmentioning
confidence: 99%
“…Nevertheless, the empirical application of this theoretical frame is often reduced to an analysis of a single life course domain. Numerous are the study focusing exclusively on either employment trajectories (Buhlmann 2008(Buhlmann , 2010Fuller and Martin 2012;Fuller and Stecy-Hildebrandt 2015;Manzoni, and Mooi-Reci 2011;Scherer 1999), education (Brzinsky-Fay 2016;Cooksey and Rindfuss 2001), household structure (Chaloupkovà 2010) or health condition (Cullati 2015;Cullati et al 2014;Friedli 2009). Equally frequent are papers that take a step further and link two life course domains.…”
Section: Theoretical Backgroundmentioning
confidence: 99%